Graphene oxide-based waveguides for enhanced self-phase modulation - Yuning Zhang; Jiayang Wu; Yang Qu; Linnan Jia; Baohua Jia; David Moss (Annals of Mathematics and Physics - Peertechz Publications, 2022)
The enhanced self-phase modulation (SPM) in silicon nitride (Si3N4) and silicon (Si) waveguides integrated with graphene oxide (GO) films is experimentally demonstrated. By using both picosecond and femtosecond optical pulses, we observe significant spectral broadening in the waveguides due to the high Kerr nonlinearity of GO films. The maximum broadening factors of up to ~3.4 and ~4.3 are achieved in GO-coated Si3N4 waveguides and GO-coated Si waveguides, respectively. The spectral broadening for femtosecond pulses is more significant than the picosecond pulses, which can be attributed to their relatively high peak power. These results show the strong potential of GO films for improving the Kerr nonlinearity of photonic devices.